Derivational Affixation In English Beauty Product Advertising Slogans: A Morphological Analysis - I Komang Sulatra; Desak Putu Eka Pratiwi; Widia Astuti; Ni Nyoman Ayu Manik Adnyani (Institut Pariwisata dan Bisnis Internasional, 2026)
Language plays strategic role in advertising, particularly through slogans used in the advertisement. Slogan as one aspect in advertisement summarizes complex brand messages into brief and memorable expressions. This study aims to examine the types of derivational affixes used in commercial slogans and to analyze their meanings and communicative purposes in advertisement. Employing a qualitative descriptive method, this research analyzes seven English slogans taken from seven beauty product advertisements, such as; Nivea, Silkygirl, Garnier, Olay, Wardah, LAKME, and Estée Lauder. These data source were taken by applying purposive sampling method through searching beauty product advertisements in the internet. The data were collected through observation method and documentation techniques by selecting words with derivational affixes found in the slogans. The data were analyzed qualitatively using Katamba’s (1993) theory of derivational morphology, particularly to derivational process using tree diagrams. The findings reveal that kinds of derivational affixes used in the slogans are prefix un- and suffix -ly, -ful, -al, -ic, -less, and -able. The finding shows suffixes are dominantly used with eight (9) data compared to prefix with only three (3) data The study concludes that derivational affixation enables advertisers to construct powerful slogans by applying derivative word to enhance persuasive language therefore future research is recommended to investigate derivational morphology in a larger corpus of advertising slogans across various product categories or digital advertising platforms.